Preparation method of electrode material, electrode material, electrode plate, battery and electric device
By mixing the transition metal oxide with the raw materials of lithium manganese iron phosphate material for calcination, the electrode material with a clad structure is solved, and the problems of poor stability and large internal resistance of nickel-cobalt-manganese ternary materials are achieved, and higher cyclic stability and lower internal resistance are achieved.
Patent Information
- Application Number
- CN202410869507.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-04-11
AI Technical Summary
The existing nickel, cobalt, manganese ternary materials have poor stability during use, are prone to failure, and have large internal resistance, resulting in poor performance of lithium-ion batteries.
By mixing the transition metal oxide with the raw material of the lithium manganese iron phosphate material for calcination, an electrode material including the inner core and two cladding layers coated outside the inner core is formed. This method improves the surface stability and conductivity of the electrode material through physical coating and the use of conductive agents.
This method effectively reduces the contact between the electrolyte and nickel-cobalt-manganese material, improves the cycle stability and safety performance of the electrode material, reduces the internal resistance of the battery, and improves the charge and discharge efficiency.
Smart Images

Figure CN119812233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and more specifically, to a method for preparing an electrode material, an electrode material, an electrode sheet, a battery and an electrical device. Background Art
[0002] In the related art, the positive electrode of a lithium-ion battery generally includes a nickel-cobalt-manganese ternary material. However, the existing nickel-cobalt-manganese ternary material has poor stability during use, is prone to failure, and has a large internal resistance.
[0003] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention
[0004] An object of the present invention is to provide a new technical solution for a method for preparing an electrode material.
[0005] According to a first aspect of the present invention, a method for preparing an electrode material is provided. The preparation method comprises:
[0006] Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material;
[0007] Mixing the first material, the core and the first conductive agent to obtain a second material, wherein the second material includes the core and a first coating layer coating the core;
[0008] A second coating layer is formed outside the first coating layer, and the second coating layer includes a conductive agent.
[0009] Optionally, the step of forming a second coating layer outside the first coating layer, wherein the second coating layer includes a conductive agent, comprises:
[0010] The second carbon-containing organic matter and the second material are mixed and calcined for a second time to obtain the electrode material, which includes an inner core, a first coating layer coated outside the inner core, and a second coating layer coated outside the first coating layer.
[0011] Optionally, the raw materials of the lithium manganese iron phosphate material include: a lithium source, a manganese source, an iron source and a phosphorus source.
[0012] Optionally, in the manganese source and the iron source, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.
[0013] Optionally, the step of mixing the transition metal oxide with the raw material of lithium iron manganese phosphate material and performing a first calcination to obtain the first material comprises:
[0014] Adding a lithium source, a manganese source, an iron source and a phosphorus source into a first solvent for dissolving to obtain a first mixed solution;
[0015] dissolving a transition metal oxide and a first carbon-containing organic matter in the first mixed solution to obtain a second mixed solution;
[0016] The second mixed solution is subjected to a first calcination to obtain the first material.
[0017] Optionally, the molar ratio of the transition metal oxide to the lithium manganese iron phosphate is a, and the molar ratio of the first carbon-containing organic matter to the lithium manganese iron phosphate is a / 3, wherein a=0.03 to 0.2.
[0018] Optionally, the temperature of the first calcination is 400° C. to 950° C., and the temperature is maintained for 1 to 3 hours when the temperature rises to the full temperature.
[0019] Optionally, the step of mixing the first material, the core and the first conductive agent to obtain the second material comprises:
[0020] Dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in a second solvent and mixing them to obtain a third mixed solution;
[0021] The mixed third mixed solution is dried.
[0022] Optionally, it also includes:
[0023] adding another portion of the first material, the dried product of the third mixed solution, and the second conductive agent into the third solvent and mixing them to obtain a fourth mixed solution;
[0024] The mixed fourth mixed solution is dried to obtain a second material.
[0025] Optionally, in the step of mixing the second carbon-containing organic matter and the second material and performing a second calcination to obtain the electrode material, the molar ratio of the second carbon-containing organic matter to the second material is b, where b=0.01 to 0.15.
[0026] Optionally, the temperature of the second calcination is 130° C. to 200° C., and when the temperature rises to an integer multiple of 50, the temperature is kept for 0.5 hour to 1.5 hours.
[0027] According to a second aspect of the present application, an electrode material is provided. The electrode material is prepared according to the preparation method provided in the present application.
[0028] According to a third aspect of the present application, an electrode sheet is provided, which comprises a sheet body and the electrode material described in the present application, wherein the electrode material is arranged on a surface of the sheet body.
[0029] According to a fourth aspect of the present application, a battery is provided, which includes the electrode sheet described in the present application.
[0030] According to a fifth aspect of the present application, an electrical device is provided, which includes the battery described in the present application, or includes the electrode sheet described in the present application, or includes the electrode material described in the present application.
[0031] According to one embodiment of the present disclosure, the preparation method is simple to operate, and the electrode material formed has stable properties. The electrode material prepared by the preparation method includes an inner core and two coating layers coated outside the inner core. The two coating layers can effectively reduce the contact between the electrolyte and the nickel-cobalt-manganese material, improve the surface stability of the electrode material, and effectively inhibit the exothermic reaction between the electrolyte and the nickel-cobalt-manganese material under abuse conditions such as overcharging, short circuit, heating and acupuncture, thereby improving the cycle stability and safety performance of the electrode material. The conductive agent can improve the conductivity of the electrode material and reduce the internal resistance of the battery.
[0032] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.
[0034] Figure 1 It is a schematic diagram of the structure of the positive electrode material according to an embodiment of the present application.
[0035] Figure 2 yes Figure 1 A partial enlarged view of .
[0036] Description of reference numerals:
[0037] 1. inner core; 2. first coating layer; 2-1. high concentration layer; 2-2. low concentration layer; 2-3. carbon material; 3. second coating layer. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.
[0039] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.
[0040] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.
[0041] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0042] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.
[0043] According to the first embodiment of the present application, a method for preparing an electrode material is provided. The preparation method comprises:
[0044] Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material;
[0045] Mixing the first material, the core and the first conductive agent to obtain a second material, wherein the second material includes the core and a first coating layer 2 coated outside the core;
[0046] A second coating layer 3 is formed outside the first coating layer 2, wherein the second coating layer includes a conductive agent.
[0047] In an embodiment of the present application, the core 1 is a ternary material, such as a nickel-cobalt-manganese material. Optionally, the ternary material includes at least one of NCM111, NCM523, NCM622, and NCM811. The core 1 is a powder, and the particle size of the core 1 is in the micron level. Optionally, the particle size of the core 1 is less than or equal to 5 μm. Further, the particle size of the core 1 is 0.5 μm to 1 μm. Within this range, the core 1 has high activity and high electrochemical stability. A first coating layer 2 is coated on the outside of the core 1, and a second coating layer 3 is coated on the outside of the first coating layer 2 by physical coating. Transition metal-doped lithium manganese iron phosphate (LiMnPO 4 , referred to as LMP) material combines the stability of olivine phosphate structure and high voltage characteristics. By doping with different transition metal oxides, lithium manganese iron phosphate material can obtain better electrochemical properties, such as high structural stability, electrical conductivity and cycle performance. The second coating layer 3 is a conductive agent. The conductive agent is used for electrical conduction, which can increase the electron conduction path inside the electrode material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery. The conductive agent helps to reduce the polarization of the electrode reaction, reduce energy loss, and increase the operating voltage of the battery. The preparation method has a simple process and can form an electrode material with stable properties.
[0048] In one example, the step of coating the core 1 to form a first coating layer 2, wherein the first coating layer 2 includes a transition metal-doped lithium manganese iron phosphate material, includes:
[0049] Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material;
[0050] The first material, the core 1 and the first conductive agent are mixed to obtain a second material, wherein the second material includes the core 1 and a first coating layer 2 coating the core 1 .
[0051] In this example, the raw materials of the lithium iron manganese phosphate material include a lithium source, a manganese source, an iron source and a phosphorus source. Optionally, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium chloride and lithium oxide. The manganese source includes at least one of manganese dioxide, manganese tetraoxide and manganese sulfate. The iron source includes at least one of ferrous sulfate, ferric nitrate, iron oxide, iron powder, ferrous oxalate and ferrous phosphate. The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate or diammonium hydrogen phosphate. Transition metal oxides are used to provide transition metal elements. Transition metal oxides are introduced in the process of preparing the lithium iron manganese phosphate material. Transition metal oxides can dope and modify the lithium iron manganese phosphate material, thereby improving the ion conductivity of the lithium iron manganese phosphate material. In addition, the transition metal oxides will also form nano metal oxides on the surface of the lithium iron manganese phosphate material. During the annealing treatment, the transition metal oxide reacts with the residual lithium carbonate, lithium hydroxide and other substances on the surface of the lithium iron manganese phosphate material to form a lithium ion conductor, thereby reducing the residual alkali content of the lithium iron manganese phosphate material, improving the ability of the lithium iron manganese phosphate material to conduct lithium ions, and enhancing the bonding force between the first coating layer 2 and the second coating layer 3. After the first calcination, a transition metal-doped lithium iron manganese phosphate material, i.e., the first material, can be formed.
[0052] During coating, the first material, the core 1 and the first conductive agent are mixed to obtain the second material, wherein the second material includes the core 1 and the first coating layer 2 coated outside the core 1. It should be noted that the particle size of the core 1 is less than or equal to 5μm. Furthermore, the particle size of the core 1 is 0.5μm to 1μm. The first material is a granular material, and its particle size is nanometer-level. For example, the particle size of the first material is less than or equal to 100μm. Since the particle size of the core 1 is larger than that of the first material, the first material can adhere to the surface of the core 1 during the mixing process. Preferably, the particle size of the first material is greater than or equal to 40μm. This particle size range is not only convenient for the coating of the first coating layer 2 on the core, but also convenient for the coating of the second coating layer 3 on the first coating layer 2.
[0053] Preferably, in order to improve the conductivity of the first material. The raw material of the lithium manganese iron phosphate material also includes a first carbon-containing organic matter. The first carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. In order to mix evenly, the raw material of the lithium manganese iron phosphate material is added to the first solvent. The first solvent includes at least one of ketone, alcohol, and water. Ketones include acetone, methyl ethyl ketone, butanone, cyclohexanone, etc. Alcohols include methanol, ethanol, propanol, ethylene glycol, etc. During preparation, the above materials are added to the first solvent and mixed. For example, mixing is performed by ultrasonic dispersion, mechanical stirring, etc.
[0054] Finally, the mixed liquid is first calcined in a muffle furnace, for example, in a nitrogen or inert gas atmosphere, to obtain a first material.
[0055] In one example, the step of forming the second coating layer 3 outside the first coating layer 2, wherein the second coating layer 3 includes a conductive agent, comprises:
[0056] The second carbon-containing organic matter and the second material are mixed and calcined for a second time to obtain the electrode material, which includes a core 1 , a first coating layer 2 coated outside the core 1 , and a second coating layer 3 coated outside the first coating layer 2 .
[0057] In this example, the second carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. The above substances can form a coating on the second material. After the second calcination, the second carbon-containing organic matter forms a conductive agent, and the conductive agent forms a second coating layer 3, and the second coating layer 3 is coated on the outside of the first coating layer 2. The conductive agent is a granular material. The particle size of the conductive agent is 20μm to 35μm. The particle size of the conductive agent is smaller than the particle size of the first material, so the second coating layer 3 can be coated on the outside of the first coating layer 2.
[0058] In one example, in the manganese source and the iron source, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.
[0059] In this example, the general formula of lithium manganese iron phosphate material is LiMn x Fe 1-x PO 4 For example, x is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9. Within this range, the manganese content in the first coating layer 2 is further reduced, the amount of manganese elution is reduced, and the performance of the first coating layer 2 is ensured to be stable.
[0060] In one example, the step of adding a lithium source, a manganese source, an iron source, a phosphorus source, a transition metal oxide, and a first carbon-containing organic matter into a first solvent for mixing, and performing a first calcination to obtain a first material includes:
[0061] Adding a lithium source, a manganese source, an iron source and a phosphorus source into a first solvent for dissolving to obtain a first mixed solution;
[0062] dissolving a transition metal oxide and a first carbon-containing organic matter in the first mixed solution to obtain a second mixed solution;
[0063] The second mixed solution is subjected to a first calcination to obtain a first material.
[0064] In this example, multiple raw materials are added in steps. For example, in the step of adding a lithium source, a manganese source, an iron source, and a phosphorus source to a first solvent for dissolution to obtain a first mixed solution, the above materials are easily dispersed in the first solvent, so the lithium source, the manganese source, the iron source, and the phosphorus source are added to the first solvent for dissolution at room temperature.
[0065] In the step of adding the lithium source, manganese source, iron source and phosphorus source to the first solvent for dissolution to obtain the first mixed solution, the transition metal oxide and the first carbon-containing organic matter are not easy to disperse in the first mixed solution, so under heating conditions, the transition metal oxide and the first carbon-containing organic matter are dispersed in the first mixed solution to obtain a second mixed solution. For example, the heating temperature is 60°C. The ultrasonic dispersion time is 0.5 hours to 1 hour. Of course, the heating temperature is not limited to 60°C, and can also be 50°C, 70°C, 80°C, etc. Those skilled in the art can set it according to actual needs.
[0066] Finally, the second mixed solution is added into the muffle furnace for the first calcination.
[0067] The first material is mixed by a multi-step dispersion method, and the quality of the final obtained first material is uniform.
[0068] In one example, the molar ratio of the transition metal oxide, the first carbon-containing organic matter and the lithium manganese iron phosphate is a, a / 3, wherein a=0.03 to 0.2.
[0069] Within this range, the transition metal oxide can effectively dope and modify the lithium manganese iron phosphate, and the first carbon-containing organic matter can enable the transition metal-doped lithium manganese iron phosphate material to form a nanomaterial.
[0070] In one example, the temperature of the first calcination is 400° C. to 950° C., and the temperature is maintained for 1 to 3 hours when the temperature is raised to the full temperature.
[0071] In this example, the first sintering temperature is within this range, which can make the transition metal doped lithium manganese iron phosphate material form nanomaterials. During the heating process, the muffle furnace is kept warm for 1 to 3 hours when the temperature rises to the full temperature. Insulation can ensure that the transition metal oxide, the first carbon-containing organic matter and the lithium manganese iron phosphate have enough time to fully react chemically at the set high temperature to form the desired compound phase. Insulation can promote the growth of the lattice of the transition metal doped lithium manganese iron phosphate material and improve the crystallinity of the material. High crystallinity helps the rapid diffusion of lithium ions. Insulation helps to form a more stable crystal structure, which can effectively improve the electrochemical performance and cycle stability of the material. Insulation can also reduce the thermal stress caused by rapid cooling, reduce the microstructural defects of the crystal structure, reduce the thermal decomposition of the material at high temperature, and maintain the chemical stability of the material. The length of the insulation time can control the microstructure of the material, including the size and shape of the grains. Insulation also helps to increase the density of the sintered body, reduce pores, and improve the energy density and power density of the battery.
[0072] For example, the temperature of the first sintering is 800°C. During the sintering process, in a nitrogen atmosphere, the temperature is stepped to 800°C at a temperature rise rate of 5°C / minute. After natural cooling, the first material is obtained, wherein the temperature step has a critical value of a whole temperature number such as 200°C to 400°C. Insulation is performed in multiple steps. For example, the room temperature is 25°C→200°C→400°C→600°C→800°C. The temperature is maintained at a constant level for 2 hours at each step. That is, the temperature is maintained at 200°C, 400°C, 600°C, and 800°C for 2 hours each. In this way, the generated transition metal-doped lithium manganese iron phosphate material has a good crystal form, few defects, small thermal stress, dense material density, good chemical stability, and high energy density and power density.
[0073] In other examples, the temperature may be kept at 100° C., 300° C., 500° C., 700° C., or 800° C. Alternatively, the temperature may be kept at 200° C., 300° C., 600° C., 700° C., or 800° C. The temperature of the keeping temperature may be set according to actual needs.
[0074] Of course, the temperature and heat preservation process of the first calcination are not limited to the above embodiments, and those skilled in the art can set them according to actual needs.
[0075] In one example, the step of mixing the first material, the core 1 and the first conductive agent to obtain the second material includes:
[0076] Dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in the second solvent, and mixing them by ultrasonic dispersion to obtain a third mixed solution;
[0077] ball milling the third mixed solution;
[0078] The third mixed solution after ball milling is spray-dried.
[0079] In this example, the nickel-cobalt-manganese material includes at least one of NCM111, NCM523, NCM622, and NCM811. The first conductive agent may be, but is not limited to, carbon material 2-3. The second solvent includes at least one of ketone, alcohol, and water. After the first material, the nickel-cobalt-manganese material, and the first conductive agent are added to the second solvent, they are mixed by mechanical stirring, ultrasonic dispersion, and the like. The mixed solution is dried by spray drying, heating drying, and the like. After drying, the second material is obtained. In the step of dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in the second solvent and mixing them by ultrasonic dispersion to obtain a third mixed solution, the second solvent is ethanol. Part of the first material, the nickel-cobalt-manganese material, and the first conductive agent are dissolved in ethanol. For example, at 60°C, ultrasonic dispersion is performed for 0.5 to 1 hour to finally obtain a third mixed solution.
[0080] In the step of ball milling the third mixed solution, the third mixed solution is ball milled. For example, the third mixed solution is added to a ball milling jar and ball milled for 2 hours. The ball milling speed is 300 rpm to 600 rpm, and the number of ball milling is 2 or 3 times.
[0081] Ball milling reduces the particle size of the raw material powder through mechanical force to form fine primary particles, which helps to increase the specific surface area of the material, thereby increasing the diffusion rate of lithium ions and improving the charge and discharge rate of the battery. Ball milling can promote the occurrence of solid-state reactions, especially in the second calcination, ball milling can increase the reaction rate and help synthesize electrode materials with specific structures and properties. Ball milling can increase the compaction density of electrode materials, reduce the gaps between particles, and help improve the energy density of batteries. Ball milling can introduce more defects and grain boundaries, which can serve as rapid diffusion channels for lithium ions and improve the conductivity of electrode materials.
[0082] Finally, the third mixed solution after ball milling is spray dried. By adjusting the parameters of spray drying, such as spray speed, hot air temperature, drying rate, etc., the particle morphology and size of the obtained electrode material powder can be controlled, thereby affecting the charge and discharge performance of the electrode material. The particles produced by spray drying usually have a smaller size and a higher specific surface area, which helps to increase the diffusion rate of lithium ions, thereby improving the charge and discharge efficiency of the battery. Spray drying can prepare electrode materials with good electrochemical properties, such as high capacity, high rate performance and excellent cycle stability.
[0083] In one example, it also includes:
[0084] adding another portion of the first material, the second material, and the second conductive agent into the third solvent, and mixing them by ultrasonic dispersion to obtain a fourth mixed solution;
[0085] ball milling the fourth mixed solution;
[0086] The fourth mixed solution after ball milling is spray-dried.
[0087] In this example, the second conductive agent includes carbon material 2-3. The third solvent includes at least one of ketone, alcohol, and water. Another part of the first material, the second material, and the second conductive agent are added to the third solvent and mixed by mechanical stirring, ultrasonic dispersion, etc. The mixed solution is dried by spray drying, heating drying, etc. After drying, the second material is obtained.
[0088] In the step of adding another portion of the first material, the second material, and the second conductive agent to the third solvent and mixing them by ultrasonic dispersion to obtain a fourth mixed solution, the third solvent is ethanol. The first material, the second material, and the second conductive agent are added to ethanol and dissolved. Ultrasonic dispersion is performed at 60° C. for 1 to 2 hours to finally obtain a fourth mixed solution.
[0089] In the step of ball milling the fourth mixed solution, the fourth mixed solution is ball milled. For example, the fourth mixed solution is added to a ball milling jar and ball milled for 2 hours. The ball milling speed is 300 to 600 rpm, and the number of ball millings is 2 or 3 times.
[0090] In the step of spray-drying the fourth mixed solution after ball milling, the fourth mixed solution after ball milling is spray-dried to obtain the second material.
[0091] In this example, by adding the first material twice, the second coating layer 3 can be formed into the high-concentration layer 2 - 1 and the low-concentration layer 2 - 2 .
[0092] Of course, more concentration gradient layers can be formed by adding the first material more times.
[0093] In one example, in the step of mixing the second carbon-containing organic matter and the second material and performing a second calcination to obtain the electrode material, the molar ratio of the second carbon-containing organic matter to the second material is b, where b=0.01 to 0.15.
[0094] Optionally, the second carbon-containing organic matter includes at least one of glucose, sucrose, fructose, cellulose, starch, etc. The fourth solvent includes at least one of ketone, alcohol, and water. Ketones include acetone, methyl ethyl ketone, butanone, cyclohexanone, etc. Alcohols include methanol, ethanol, propanol, ethylene glycol, etc. After the second material and the second carbon-containing organic matter are added to the fourth solvent, they are mixed by mechanical stirring, ultrasonic dispersion, etc. The mixed solution is added to a muffle furnace and calcined for the second time in an inert gas or nitrogen atmosphere. After the second calcination, the electrode material described in the present application is obtained.
[0095] For example, the second carbon-containing organic matter is glucose. The fourth solvent is ethanol. For example, the solution after the second material, the second carbon-containing organic matter and the fourth solvent are mixed is ultrasonically dispersed at 60° C. for 1 to 2 hours. Then, the ultrasonically dispersed solution is placed in a muffle furnace for a second calcination.
[0096] The molar ratio of the second carbon-containing organic matter to the second material is b, b=0.01 to 0.15. For example, the molar ratio of glucose to the second material is 0.01 to 0.15. Glucose is converted into carbon material 2-3 during high-temperature calcination. Carbon material 2-3 acts as a conductive agent, i.e., the second coating layer 3. Within this range, the thickness of the second coating layer 3 is uniform and has few defects. For example, when the thickness is within the above thickness range, the second coating layer 3 significantly improves the electrical conductivity of the electrode material, thereby reducing the internal resistance of the battery. The second coating layer 3 can serve as a protective layer, reducing the side reactions of the electrode material with the electrolyte during the charge and discharge process, thereby improving the cycle stability of the battery. The second coating layer 3 helps to form a stable chemical and electrochemical reaction interface on the surface of the electrode material, reducing the decomposition of the electrolyte. The second coating layer 3 can also buffer the volume change of the electrode material during the charge and discharge process, reduce structural stress, and improve the structural stability of the electrode material.
[0097] In one example, the temperature of the second calcination is 700° C. to 1000° C., and when the temperature rises to an integer multiple of 100, the temperature is kept for 0.5 hour to 1.5 hours.
[0098] In this example, the calcination atmosphere of the muffle furnace is nitrogen, and the temperature is increased stepwise to 700°C at a temperature increase rate of 5°C / min. The temperature is kept at 700°C. After natural cooling, the electrode material is obtained. In the second calcination process, for example, the room temperature is 25°C. The temperature increase process is 25°C→100°C→200°C→300°C→400°C→500°C→600°C→700°C. At each step, i.e., 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, and 700°C, each temperature is kept constant for 1 hour, and finally the electrode material is obtained.
[0099] In this example, through the second calcination, a core-shell structure electrode material containing a core 1 of nickel-cobalt-manganese material, a transition metal-doped lithium manganese iron phosphate material as a first coating layer 2, and a conductive agent as a second coating layer 3 is finally obtained.
[0100] Of course, in the above steps, when performing ultrasonic dispersion, the heating temperature is not limited to 60° C., but can also be 50° C., 70° C., 80° C., etc. Those skilled in the art can set it according to actual needs.
[0101] In the embodiment of the present application, a lithium source, a manganese source, an iron source, a phosphorus source, a transition metal oxide and a first carbon-containing organic matter are subjected to a first calcination to prepare nano-manganese iron lithium phosphate, wherein manganese and iron exist in the form of divalent ions. The anion is phosphate. During the sintering process, there is no need to perform a reduction process, thereby reducing the structural defects of the electrode material caused by the reduction of Mn and Fe during the preparation process of the electrode material.
[0102] Transition metal oxides are introduced in the process of preparing lithium iron manganese phosphate materials. Transition metal oxides can dope and modify lithium iron manganese phosphate materials, thereby improving the ion conductivity of lithium iron manganese phosphate materials. In addition, transition metal oxides will also form nano metal oxides on the surface of lithium iron manganese phosphate materials. During annealing, the transition metal oxides react with residual lithium carbonate, lithium hydroxide and other substances on the surface of the lithium iron manganese phosphate material to form lithium ion conductors, thereby reducing the residual alkali content of the lithium iron manganese phosphate material, improving the ability of the lithium iron manganese phosphate material to conduct lithium ions, and enhancing the bonding force between the first coating layer 2 and the second coating layer 3.
[0103] The gap between the transition metal oxide doped lithium manganese iron phosphate material and the nickel cobalt manganese material is filled with a conductive agent. The conductive agent can improve the ionic conductivity of the electrode material, and at the same time can effectively avoid direct contact between the transition metal oxide doped lithium manganese iron phosphate material and the nickel cobalt manganese material, prevent spontaneous redox reaction between the two, and improve the interface structure stability of the electrode material. At the same time, the above structure can isolate moisture, reduce the sensitivity of the nickel cobalt manganese material to environmental humidity, and improve the storage and processing performance of the electrode material during use.
[0104] In addition, the first coating layer 2 and the second coating layer 3 can effectively reduce the contact between the electrolyte and the nickel-cobalt-manganese material, improve the stability of the surface structure of the electrode material, and effectively inhibit the exothermic reaction between the electrolyte and the nickel-cobalt-manganese material under conditions of overcharging, short circuit, heating and puncture, thereby improving the cycle and safety performance of the electrode material.
[0105] In addition, secondary coating is performed by mechanical processing, so that the transition metal oxide-doped lithium iron manganese phosphate material can be uniformly and tightly coated on the surface of the nickel-cobalt-manganese material. The preparation method is simple, efficient, and suitable for industrial production. According to the second embodiment of the present application, an electrode material is provided. The electrode material is prepared according to the above-mentioned preparation method. The electrode material includes a core 1 containing a nickel-cobalt-manganese material, a first coating layer 2 coated outside the core 1, and a second coating layer 3 coated outside the first coating layer 2, the first coating layer 2 includes a transition metal-doped lithium iron manganese phosphate material, and the second coating layer 3 includes a conductive agent.
[0106] like Figure 1 , Figure 2 As shown, the electrode material is used as a positive electrode material. The electrode material is a core-shell structure. The core 1 is a ternary material, that is, a nickel-cobalt-manganese material. Optionally, the ternary material includes at least one of NCM111, NCM523, NCM622, and NCM811. The first coating layer 2 is coated outside the core 1. Transition metal-doped lithium manganese iron phosphate (LiMnPO 4 , referred to as LMP) material combines the stability of olivine phosphate structure and high voltage characteristics. By doping with different transition metal oxides, lithium manganese iron phosphate material can obtain better electrochemical properties, such as high structural stability, electrical conductivity and cycle performance. The second coating layer 3 is a conductive agent. The conductive agent is used for electrical conduction, which can increase the electron conduction path inside the electrode material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery. The conductive agent helps to reduce the polarization of the electrode reaction, reduce energy loss, and increase the operating voltage of the battery.
[0107] The electrode material is in granular form. The average particle size of the core-shell structure is less than or equal to 10 μm. Within this range, the core-shell structure has high structural strength and excellent electrochemical performance. Further, the average particle size is 200 nm to 2 μm, within this range, the electrochemical performance of the electrode material is even better.
[0108] The thickness of the first coating layer 2 is 1 nm to 100 nm, preferably 10 nm to 80 nm. The thickness of the second coating layer 3 is 10 nm to 50 nm, preferably 20 nm to 35 nm. Within the above range, the two coating layers provide good protection for the core 1.
[0109] In the embodiment of the present application, the electrode material includes a core 1 and two coating layers coated outside the core 1. The two coating layers can effectively reduce the contact between the electrolyte and the nickel-cobalt-manganese material, improve the surface stability of the electrode material, and effectively inhibit the exothermic reaction between the electrolyte and the nickel-cobalt-manganese material under abuse conditions such as overcharging, short circuit, heating and acupuncture, thereby improving the cycle stability and safety performance of the electrode material. The conductive agent can improve the conductivity of the electrode material and reduce the internal resistance of the battery.
[0110] In one example, the first coating layer 2 includes a conductive agent, and the transition metal-doped lithium manganese iron phosphate material is mixed with the conductive agent.
[0111] In this example, transition metal-doped lithium manganese iron phosphate material forms particles. The gaps between the particles are filled with a conductive agent. The conductive agent can further increase the electron conduction path inside the electrode material, reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery.
[0112] Furthermore, the nickel-cobalt-manganese material as the core 1 is formed into particles. Conductive agent is also filled between the particles. This arrangement can further reduce the internal resistance of the battery, improve the charge and discharge efficiency of the battery, and improve the rate performance and cycle stability of the battery.
[0113] In one example, the conductive agent includes carbon material 2-3. Carbon material 2-3 has good conductivity and can form a good combination with nickel-cobalt-manganese material and transition metal-doped lithium manganese iron phosphate material.
[0114] Of course, the conductive agent is not limited to the carbon material 2-3, and may also be a conductive polymer, etc. Those skilled in the art may set it according to actual needs.
[0115] In one example, the carbon material 2-3 includes at least one of a point-shaped carbon material 2-3 and a linear carbon material 2-3.
[0116] Optionally, the point-shaped carbon material 2-3 includes at least one of carbon black, acetylene black, Ketjen black and conductive graphite. The linear carbon material 2-3 includes at least one of carbon fiber and carbon nanotubes. The linear carbon material 2-3 has high strength and toughness, can improve the mechanical properties of the electrode material, and prevent deformation or breakage of the electrode material during charging and discharging. The addition of the point-shaped carbon material 2-3 can also further enhance the structural stability of the electrode material.
[0117] Preferably, the carbon material 2-3 includes point-shaped carbon material 2-3 and linear carbon material 2-3. Since the linear carbon material 2-3 and the point-shaped carbon material 2-3 have excellent conductivity, mixing them together can effectively reduce the internal resistance of the electrode material, improve the charge and discharge efficiency of the battery, and increase the energy density of the battery.
[0118] Of course, the carbon materials 2-3 are not limited to the above embodiments, and those skilled in the art can configure them according to actual needs.
[0119] In one example, along the thickness direction of the electrode material, the concentration of the transition metal-doped lithium manganese iron phosphate material in the first coating layer 2 gradually decreases from a side close to the core 1 to a side close to the second coating layer 3 .
[0120] In this example, the concentration of the transition metal-doped lithium iron manganese phosphate material in the first coating layer 2 gradually decreases from the inside to the outside. The concentration of the conductive agent in the first coating layer 2 gradually increases from the inside to the outside. In this way, the closer the first coating layer 2 is to the outer layer, the better the electron transport performance, thereby effectively improving the conductivity of the electrode material. The closer the first coating layer 2 is to the inner layer, the higher the concentration of the lithium iron manganese phosphate material and the higher the energy density. In this way, the electrode material can effectively take into account both high energy density and high conductivity.
[0121] For example, Figure 1 to Figure 2 As shown, the portion of the first coating layer 2 close to the core 1 forms a high concentration layer 2-1, and the portion close to the second coating layer 3 forms a low concentration layer 2-2. The concentration of the transition metal-doped lithium manganese iron phosphate material in the high concentration layer 2-1 is high. The concentration of the transition metal-doped lithium manganese iron phosphate material in the low concentration layer 2-2 is low. The electrode material can more effectively take into account both high energy density and high conductivity.
[0122] In one example, the transition metal oxide includes a divalent transition metal oxide.
[0123] In this example, the divalent transition metal oxide introduced into the lithium manganese iron phosphate material can play a doping and modification role on the lithium manganese iron phosphate material, so that the ion conductivity of the lithium manganese iron phosphate material is significantly improved.
[0124] In addition, the divalent transition metal-doped lithium iron manganese phosphate material will form nano metal oxides, such as nano-sized divalent transition metal oxides, on the surface of the lithium iron manganese phosphate. During the annealing treatment, the nano-sized divalent transition metal oxides react with the residual lithium carbonate, lithium hydroxide and other materials on the surface of the lithium iron manganese phosphate material to form a lithium ion conductor, thereby reducing the residual alkali content of the lithium iron manganese phosphate material, and improving the ability of the lithium iron manganese phosphate material to conduct lithium ions, and enhancing the bonding force between the first coating layer 2 and the second coating layer 3.
[0125] Optionally, the divalent transition metal oxide includes at least one of beryllium oxide, magnesium oxide and calcium oxide.
[0126] In this example, the above materials have good stability, can effectively reduce the residual alkali content of the lithium manganese iron phosphate material, improve the ability of the lithium manganese iron phosphate material to conduct lithium ions, and enhance the bonding force between the first coating layer 2 and the second coating layer 3.
[0127] In one example, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.9.
[0128] In this example, the general formula of lithium manganese iron phosphate material is LiMn x Fe 1-x PO 4 For example, x is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9. Within this range, the manganese content in the first coating layer 2 is further reduced, the amount of manganese leaching is reduced, and the performance of the first coating layer 2 is ensured to be stable.
[0129] In one example, in the transition metal-doped lithium manganese iron phosphate material, the molar ratio of the transition metal to the lithium manganese iron phosphate material is 0.1% to 10%.
[0130] Within this range, the divalent transition metal oxide can effectively reduce the residual alkali content of the lithium manganese iron phosphate material, improve the ability of the lithium manganese iron phosphate material to conduct lithium ions, and enhance the bonding force between the first coating layer 2 and the second coating layer 3 .
[0131] According to a third embodiment of the present application, an electrode sheet is provided, which includes a sheet body and the electrode material described in the present application, wherein the electrode material is disposed on a surface of the sheet body.
[0132] The sheet body is a metal foil. The material of the sheet body is copper, aluminum, nickel, etc. The electrode material of the present application is coated on the surface of the metal foil by coating. The physical and chemical properties of the electrode sheet are stable.
[0133] According to a fourth embodiment of the present application, a battery is provided, which includes the electrode sheet described in the present application.
[0134] For example, the electrode sheet is a positive electrode sheet. When in use, the electrode active material of the negative electrode sheet is graphite. A separator is provided between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet, the separator and the negative electrode sheet are combined together by stacking or winding.
[0135] The battery has the characteristics of stable performance, high energy density and long service life.
[0136] According to a fifth embodiment of the present application, an electrical device is provided, which is the battery described in the present application, or includes the electrode sheet described in the present application, or includes the electrode material described in the present application.
[0137] The electrical device has the characteristics of stable performance and long service life.
[0138] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.
[0139] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.
Claims
1. A method for preparing an electrode material, characterized in that: include: Mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material, and performing a first calcination to obtain a first material; Mixing the first material, the core and the first conductive agent to obtain a second material, wherein the second material includes the core and a first coating layer coating the core; A second coating layer is formed outside the first coating layer, and the second coating layer includes a conductive agent.
2. The preparation method according to claim 1, characterized in that: The step of forming a second coating layer outside the first coating layer, wherein the second coating layer includes a conductive agent, comprises: The second carbon-containing organic matter and the second material are mixed and calcined for a second time to obtain the electrode material, which includes an inner core, a first coating layer coated outside the inner core, and a second coating layer coated outside the first coating layer.
3. The preparation method according to claim 1, characterized in that: The raw materials of the lithium manganese iron phosphate material include: a lithium source, a manganese source, an iron source and a phosphorus source.
4. The preparation method according to claim 3, characterized in that: In the manganese source and the iron source, the molar ratio of manganese to iron is x:(1-x), wherein x=0.3 to 0.
9.
5. The preparation method according to claim 3, characterized in that: The step of mixing the raw materials of the transition metal oxide and the lithium iron manganese phosphate material and performing a first calcination to obtain the first material comprises: Adding a lithium source, a manganese source, an iron source and a phosphorus source into a first solvent for dissolving to obtain a first mixed solution; dissolving a transition metal oxide and a first carbon-containing organic matter in the first mixed solution to obtain a second mixed solution; The second mixed solution is subjected to a first calcination to obtain the first material.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the transition metal oxide to the lithium manganese iron phosphate is a, and the molar ratio of the first carbon-containing organic matter to the lithium manganese iron phosphate is a / 3, wherein a=0.03 to 0.
2.
7. The preparation method according to claim 1, characterized in that: The temperature of the first calcination is 400°C to 950°C, and the temperature is kept at this temperature for 1 to 3 hours when the temperature rises to the full temperature.
8. The preparation method according to claim 1, characterized in that: The step of mixing the first material, the core and the first conductive agent to obtain the second material comprises: Dissolving part of the first material, the nickel-cobalt-manganese material, and the first conductive agent in a second solvent and mixing them to obtain a third mixed solution; The mixed third mixed solution is dried.
9. The preparation method according to claim 8, characterized in that: Also includes: adding another portion of the first material, the dried product of the third mixed solution, and the second conductive agent into the third solvent and mixing them to obtain a fourth mixed solution; The mixed fourth mixed solution is dried to obtain a second material.
10. The preparation method according to claim 2, characterized in that: In the step of mixing the second carbon-containing organic matter and the second material and performing a second calcination to obtain the electrode material, the molar ratio of the second carbon-containing organic matter to the second material is b, where b=0.01 to 0.
15.
11. The preparation method according to claim 2, characterized in that: The temperature of the second calcination is 700° C. to 1000° C., and when the temperature rises to an integral multiple of 100, the temperature is kept for 0.5 hour to 1.5 hours.
12. An electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 11.
13. An electrode sheet, characterized in that: The invention comprises a sheet body and the electrode material as claimed in claim 12, wherein the electrode material is arranged on the surface of the sheet body.
14. A battery, characterized in that: Comprising the electrode sheet as claimed in claim 13.
15. An electrical device, characterized in that: A battery as claimed in claim 14, or an electrode sheet as claimed in claim 13, or an electrode material as claimed in claim 12.